Pengembangan Bahan Ajar Micro Teaching Untuk Melatih Kompetensi Pedagogik Calon Guru - Satutik Rahayu; I Gde Mertha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
Physics Education Student is a FKIP student who is printed to become a professional Physics teacher candidate. The competencies that must be possessed by professional teachers are pedagogic competence (ability to manage learning). As a prospective teacher who takes microteaching courses must master and have pedagogic competence. Pedagogic competence training can be done by trained eight basic teaching skills. In order for students to master the eight basic skills of teaching it is necessary to develop microteaching teaching materials. This research is a multi-year research with the type of research is development research following 4D model. The purpose of this research is to develop microteaching teaching materials that have been tested the level of feasibility. Data analysis uses expert validation sheets and user responses. The result of the research shows that the teaching material of micro teaching that has been developed is in good category.